A child's first book about play therapy - Nemiroff, Marc A.; Annunziata, Jane; Scott, Margaret (Washington : American Psychological Association, 1990)
Readers learn about psychotherapy and the value of play as treatment for behavior problems in small children
'This book is intended for young children, ages 4 to 7 or so'--P. 3.
Keywords: Play therapy -- Juvenile literature; Child psychotherapy -- Juvenile literature; Play Theraphy -- literature; Psychotheraphy -- in infancy and childhood; Child psychiatry